Differential subcellular distribution of tubulin epitopes in boar spermatozoa: recognition of class III beta-tubulin epitope in sperm tail - Pĕknicová, J; Kubátová, A; Sulimenko, V; Dráberová, E; Viklický, V; Hozák, P; Dráber, P (Biology of reproduction, 2001)
The exposure of tubulin epitopes was studied in ejaculated boar spermatozoa using a panel of four monoclonal antibodies specific to the N-terminal or C-terminal structural domains of tubulin and three monoclonal antibodies against class III beta-tubulin. The specificity of the antibodies was confirmed by immunoblotting. Immunocytochemical staining showed that antibodies discriminated between various parts of a spermatozoon, and that epitopes of class III beta-tubulin were present in the flagellum. A tubulin epitope from the C-terminal domain of beta-tubulin was detected in the triangular segment of the postacrosomal part of the sperm head. Its distribution changed after an A23187 ionophore-induced acrosome reaction, indicating that tubulin participates in the early stages of fertilization. Three monoclonal antibodies, TU-20, SDL.3D10, and TUJ1 directed against epitopes on the C-terminal end of neuron-specific class III beta-tubulin that is widely used as a neuronal marker, stained the flagella. The reactivity of TU-20 was further confirmed by absorbing the antibody with the immunizing peptide and by immunoelectron microscopy. Immunoblotting after two-dimensional electrophoresis revealed that the corresponding epitope was not present on all beta-tubulin isoforms. These results suggest that various tubulins are involved in the functional organization of the mammalian sperm flagellum and head.
Keywords: Sperm Tail; specificita protilátek; akrozomální reakce; sekvence aminokyselin; lidé; imunoblotting; monoklonální protilátky; mužské pohlaví; Acrosome Reaction; Antibodies, Monoclonal; bičík spermie; Peptide Fragments; Swine; Immunoblotting; Tubulin; zvířata; Humans; fluorescenční protilátková technika; Amino Acid Sequence; peptidové fragmenty; Microscopy, Immunoelectron; Antibody Specificity; Fluorescent Antibody Technique; prasata; tubulin; Spermatozoa; Epitopes; imunoelektronová mikroskopie; spermie; Male; epitopy; Animals